A competitive PCR‐based method to detect a single copy of T‐DNA insertion in transformants. Issue 3 (2nd August 2021) - Fan, Hua; Huang, Liu‐Yuan; Tong, Xin; Yang, Liu‐Jie; Shi, Jiao‐Jiao; Jiao, Jiao; Xu, Hua‐Quan; Li, Ying‐Chao; Wang, Dan‐Yang
Abstract: Gene function studies benefit from the availability of mutants. In plants, Agrobacterium ‐mediated genetic transformation is widely used to create mutants. These mutants, also called transformants, contain one or several transfer‐DNA (T‐DNA) copies in the host genome. Quantifying the copy number of T‐DNA in transformants is beneficial to assess the number of mutated genes. Here, we developed a competitive polymerase chain reaction (PCR)‐based method to detect a single copy of a T‐DNA insertion in transformants. The competitor line BHK − ‐1 that contains a single copy of competitor BHK − ( BHK, Basta, Hygromycin, Kanamycin‐resistant genes) was crossed with test transformants and the genomic DNA of F1 plants was subjected to competitive PCR. By analyzing the gray ratio between two PCR products, we were able to determine whether or not the test transformants contained a single copy of T‐DNA insertion. We also generated the control lines BHK ±1:1 and BHK ±2:1, which contain the target ( BHK + ) and competitor ( BHK − ) in a ratio of 1:1 and 2:1, respectively. The ratios of their PCR products are useful references for quantitative analysis. Overall, this method is reliable and simple in experimental manipulations and can be used as a substitute for Southern‐blot analysis to identify a single copy of T‐DNA insertion in transformants.